2001
DOI: 10.1677/joe.0.1700441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of estrogen on calcium and sodium transport by the nephron luminal membranes

Abstract: Estrogens are widely used for contraception and osteoporosis prevention. The aim of the present study was to investigate the effect of 17 -estradiol on calcium (Ca 2+ ) transport by the nephron luminal membranes, independently of any other Ca 2+ -regulating hormones. Proximal and distal tubules of rabbit kidneys were incubated with 17 -estradiol or the carrier for various periods of time, and the luminal membranes of these tubules were purified and vesiculated. Ca 2+ uptake by membrane vesicles was measured us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
2

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 38 publications
(20 reference statements)
0
31
0
2
Order By: Relevance
“…In animal models, estradiol increases sodium uptake through the luminal membranes of both proximal and distal tubules and the presence of estrogen receptors has been confirmed at both sites (52). The role of estrogen in renal salt handling was also demonstrated by Chappell et al (53) using female mRen(2) Lewis strain rats.…”
Section: Changes In Sodium and Water Handlingmentioning
confidence: 78%
“…In animal models, estradiol increases sodium uptake through the luminal membranes of both proximal and distal tubules and the presence of estrogen receptors has been confirmed at both sites (52). The role of estrogen in renal salt handling was also demonstrated by Chappell et al (53) using female mRen(2) Lewis strain rats.…”
Section: Changes In Sodium and Water Handlingmentioning
confidence: 78%
“…Those findings were documented in experiments performed on women taking oral contraceptives, as well as in rats, dogs and rabbits treated with estrogen [17,36]. This phenomenon is associated with an increase in renal reabsorption of sodium and chloride from both proximal and distal nephrons; however, the exact mechanisms involved have not yet been identified [4]. Additional evidence for the involvement of sex hormones in renal fluid balance comes from the observation that occurs an expansion of maternal ECFV associated with an increase in renal reabsorption of water, sodium and chloride mainly in pregnant rats between 5-12 days after mating, the period when the plasma levels of estrogen are increased [2].…”
Section: Introductionmentioning
confidence: 95%
“…It is well known that estrogen administration can lead to significant body fluid retention [17,18] and in very high doses it can cause hypertension [23,40]. Several investigators have shown that estrogen is associated with a decrease in urinary excretion of sodium and chloride leading to water body retention and a consequent increase in body weight [4,23,32,40]. Those findings were documented in experiments performed on women taking oral contraceptives, as well as in rats, dogs and rabbits treated with estrogen [17,36].…”
Section: Introductionmentioning
confidence: 97%
“…For example, E2 is a crucial player in the prevention of female bone decalcification resulting in osteoporosis (1), and the reduced circulating E2 level is known to be associated with an increased risk of renal stone formation in women after menopause (24). Furthermore, E2-induced fluid retention is caused partly by increased renal tubular Na ϩ reabsorption (8), and P4 has natriuretic actions by directly antagonizing aldosterone at the level of the mineralocorticoid receptors (37). In addition to long-term effects, many steroid hormones exert nongenomic effects either via their classic receptors or through membrane-associated receptors (reviewed in Ref.…”
mentioning
confidence: 99%